Expression of linguistic, ethnic and national identity in early multilingual paremiography - Jesenšek, Vida (Slavia Centralis, 2025)
The article discusses expression of linguistic, ethnic and national identity in early European multilingual paremiography to which Constantin von Wurzbach (1818–1893) born in Ljubljana made a significant contribution by his paremiographic approach, as he included Slovene in his early paremiographic works. This research focuses on the macro- and microstructure of Wurzbach’s collection of proverbs entitled Polnische Sprichwörter: Erläutert und mit ähnlichen andrer Nationen verglichen (1846) as well as on Slovenian paremiological material in the collection Die Sprichwörter der Polen historisch erläutert (1852). According to phraseological and lexicographic studies, this is an original and previously rarely used approach to researching proverbs from dictionary, linguistic and cultural-historical aspects. In the Slovenia scientific space, Wurzbach’s paremiographic approach has so far not witnessed an adequate discussion.
Keywords: proverb; paremiography; Constantin von Wurzbach; linguistic identity; national identity; ethnic identity